Emotional recognition in children and adolescents with callous-unemotional trait: A systematic review of eye-tracking studies - Moreno-Albalat, María Isabel; Sánchez-Jiménez, Virginia (Psychology, Society & Education, 2025)
Callous-unemotional or emotional insensitivity is an individual trait characterized by a lack of guilt and remorse, absence of empathy, and lack of concern for the feelings of others, among other characteristics. Published works have shown that the child and adolescent population presents difficulties in emotional recognition, although not all works conclude whether this difficulty is generalized to all emotions or is restricted to specific emotions. The use of methodologies such as eye-tracking in these studies is helping to advance this line of research, allowing us to determine which attentional processes are involved in these difficulties and in which specific emotions they occur. However, this line of research is incipient, so the objective of this systematic review has been to analyze and organize the existing information on the difficulties in emotional recognition presented by children and adolescents with high levels of callous-unemotional in the published articles on this topic that use eye-tracking. Following the PRISMA Declaration, four databases were reviewed (ProQuest, ERIC, Scopus, and Web of Science), obtaining 140 results, of which only 15 were included and analyzed. The analysis obtained as a result a confirmation and characterization of this deficit, finding difficulties in the recognition of negative emotions, fundamentally those of fear, anger, and sadness, with a high percentage of studies pointing out on the basis of this the difficulties of attentional focus found in these emotions, although the existence of other processes that could explain these difficulties was not rule out.